2014
DOI: 10.2139/ssrn.2506800
|View full text |Cite
|
Sign up to set email alerts
|

Debt Financing, Survival, and Growth of Start-Up Firms

Abstract: Abstract:We use data from the Kauffman Firm Surveys to analyze how the initial capital-structure decision of a U.S. start-up firm affects its subsequent survival and growth prospects. First, we analyze whether start-up capital structure explains whether or not a firm will remain in business after its first three years. We find that a firm using debt in its capital structure, and, in particular, business debt, is significantly more likely to survive. Second, we analyze whether start-up capital structure explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 31 publications
4
43
0
1
Order By: Relevance
“…Research shows that such business loans positively affect survival and growth (Cumming and Groh 2018;Cole and Sokolyk 2018). Similarly, Landström and Mason (2016) show that early-stage external equity finance matters for nonfinancial reasons.…”
Section: Growing Firmmentioning
confidence: 98%
See 1 more Smart Citation
“…Research shows that such business loans positively affect survival and growth (Cumming and Groh 2018;Cole and Sokolyk 2018). Similarly, Landström and Mason (2016) show that early-stage external equity finance matters for nonfinancial reasons.…”
Section: Growing Firmmentioning
confidence: 98%
“…In this experimental stage, uncertainty is high and equity financing is critical, but debt financing can also play an important role. A study covering the USA, the UK, Germany, and Italy found that up to 10% of start-ups acquired loans in their first or second round of funding (Held et al 2018b), and debt-financed ventures also tend to do well in terms of innovation and growth, as long as the debt is not the personal debt of the founder (Cole and Sokolyk 2018).…”
Section: Growing Firmmentioning
confidence: 99%
“…Robb and Robinson (2014) are likely the first to extensively describe the different typologies of debt for start-ups in the US. They show that bank debt is by and large the most important financing source for start-ups, while Cole and Sokolyk (2018) indicate that 76% of firms use some type of credit instrument at inception and argue that business and personal debt are fundamentally different.…”
Section: The Signaling Value Of Debt Typesmentioning
confidence: 99%
“…In many cases, lenders may not know that the loan will be transferred to the funding of a start-up. On the other hand, business debt is subject to greater scrutiny at contracting stages and more intensive monitoring and control ex post (Cole and Sokolyk, 2018). Since outside investors are less interested in the owner's creditworthiness, but more so in the screening of firm prospects and the governance that a successful loan granting imposes, business debt encompasses more valuable informational attributes.…”
Section: The Signaling Value Of Debt Typesmentioning
confidence: 99%
“…Firm characteristics that have sometimes been found to be important include a variety of 23 For recent reviews, see Mach and Wolken (2012) and Balcaen and Ooghe (2006). Other interesting and relatively recent work includes Cole andSokolyk (2014 and, Hunter (2011), Liao et al (2008/09), Ooghe and Prijker (2008), Strotmann (2007), Cressy (2006), Headd (2003), Honjo (2000), and Everett and Watson (1998).…”
Section: Small Business Survival Failure and Creationmentioning
confidence: 99%